Evaluation Of Fiscal Policy Transmission On External Balance Through The Current Account Balance In Indonesia - Jordan Putra Cahyono; Muhammad Haniffirza Usman; Rio Saputra Simanjuntak; Belantika Aplugi (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study examines the impact of government budget shocks on the current account balance (CAB) in Indonesia, addressing the gap in understanding the short-term effects of fiscal policy on external balance. Using annual time-series data from 1981 to 2024, the research applies an Ordinary Least Squares (OLS) model to analyze the relationship between government expenditure and CAB. Key findings reveal that government consumption expenditure (GGFCE) has a significant positive effect on CAB, with a coefficient of 0.136, suggesting that a 1% increase in government spending improves the current account balance by 0.136% of GDP. Conversely, gross fixed capital formation (GFCF) has a significant negative effect on CAB with a coefficient of -0.181, indicating that higher domestic investment, reliant on imported capital goods, worsens the current account deficit. These findings highlight the importance of balancing fiscal expansion with strategic spending. Theoretical implications suggest that fiscal policy's impact on the current account is mediated by both domestic consumption and trade flows. From a policy perspective, the study recommends that Indonesia’s fiscal strategy focus on export-oriented sectors, such as manufacturing and renewable energy, while controlling non-productive consumption and intensive imports. This approach can strengthen Indonesia’s economic resilience to external shocks and improve its external balance.